Comparative Inference of Duplicated Genes Produced by Polyploidization in Soybean Genome - Yanmei Yang; Jinpeng Wang; Jianyong Di (International Journal of Genomics)
Soybean (Glycine max) is one of the most important crop plants for providing protein and oil. It is important to investigate soybean genome for its economic and scientific value. Polyploidy is a widespread and recursive phenomenon during plant evolution, and it could generate massive duplicated genes which is an important resource for genetic innovation. Improved sequence alignment criteria and statistical analysis are used to identify and characterize duplicated genes produced by polyploidization in soybean. Based on the collinearity method, duplicated genes by whole genome duplication account for 70.3% in soybean. From the statistical analysis of the molecular distances between duplicated genes, our study indicates that the whole genome duplication event occurred more than once in the genome evolution of soybean, which is often distributed near the ends of chromosomes.